Perceived Barriers Affecting Adherence to Healthy Eating and Exercise Guidelines among Obese Active-Duty Military Personnel of the South African National Defence Force - Alcock, Magdeline; Wolvaardt, Jacqueline (Scientia Militaria - South African Journal of Military Studies, 2023)
The World Health Organization defines overweight and obesity as an excessive or a disproportionate accumulation of body fat that impairs health. The South African military community is a subset of the general population, and is not exempt from the effects of overweight and obesity. Military recruitment and operational preparedness are directly affected by obesity as it affects members’ physical fitness, overall health, and capacity to perform duties optimally. The South African Military Health Services uses a multidisciplinary approach for the treatment and prevention of obesity and related conditions. Assessing perceived barriers to physical activity and healthy eating within the military environment could contribute to the development of effective and relevant programmes to address weight management and mitigate the health consequences of obesity. The current cross-sectional study was conducted in Bloemfontein, and comprised 58 randomly selected active-duty military personnel diagnosed with obesity, who completed a self-administered questionnaire. Correlation analysis was used to investigate the association between continuous data by calculating the Pearson’s correlation coefficient. Analytical statistics, namely the independent T-test or analysis of the variance, was used to compare mean values among groups. The five items identified as barriers to healthy eating habits were liking food too much, difficulty controlling cravings, staying motivated, perceiving healthy food to be expensive, and a lack of will power. The five items identified as barriers to physical activity were a lack of will power to get started, social activities that do not include physical activity, a lack of physical training centres and shower facilities at work, no motivation to stick to a plan for healthy eating, and being too busy. Factors related to the military environment did not affect perceived barriers. A multidisciplinary and coordinated approach might enable the target population to attain better health outcomes, as the identified barriers were related to social and environmental factors and perceptions of self-efficacy. Further investigation into the enablers and motivators of behaviour change in this population would shed more light on addressing the apparent lack of motivation that persists among active-duty military personnel.